Preparing Medical Specialists for Genomic Medicine: Continuing Education Should Include Opportunities for Experiential Learning - McClaren, Belinda J.; Crellin, Erin; Janinski, Monika; Nisselle, Amy E.; Ng, Larissa; Metcalfe, Sylvia A.; Gaff, Clara L. (Frontiers in Genetics, 2020)
With the demand for genomic investigations increasing, medical specialists will need to, and are beginning to, practice genomic medicine. The need for medical specialists from diverse specialties to be ready to appropriately practice genomic medicine is widely recognised, but existing studies focus on single specialties or clinical settings. We explored continuing education needs in genomic medicine of a wide range of medical specialists (excluding genetic specialists) from across Australia. Interviews were conducted with 86 medical specialists in Australia from diverse medical specialties. Inductive content analysis categorised participants by career stage and genomics experience. Themes related to education needs were identified through constant comparison and discussion between authors of emerging concepts. Our findings show that participants believe that experiential learning in genomic medicine is necessary to develop the confidence and skills needed for clinical care. The main themes reported are: tailoring of education to the specialty and the individual; peer interactions contextualizes knowledge; experience will aid in developing confidence and skills. In fact, avenues of gaining experience may result in increased engagement with continuing education in genomic medicine as specialists are exposed to relevant applications in their clinical practice. Participants affirmed the need for continuing education in genomic medicine but identified that it would need to be tailored to the specialty and the individual: one size does not fit all, so a multifaceted approached is needed. Participants infrequently attended formal continuing education in genomic medicine. More commonly, they reported experiential learning by observation, case-review or interacting with a ‘genomics champion’ in their specialty, which contextualized their knowledge. Medical specialists anticipate that genomic medicine will become part of their practice which could lessen demand on the specialist genetic workforce. They expect to look to experts within their own medical specialty who have gained genomics expertise for specific and contextualised support as they develop the skills and confidence to practice genomic medicine. These findings highlight the need to include opportunities for experiential learning in continuing education. Concepts identified in these interviews can be tested with a larger sample of medical specialists to ascertain representativeness